Determination of radionuclide concentration and radiological hazard in soil and water near the uranium tailings reservoir in China. Issue 1 (1st January 2021) - Liu, Yuanyuan; Zhou, Weibo; Gao, Bai; Zheng, Zhihong; Chen, Gongxin; Wei, Qianglin; He, Ying
ABSTRACT: Radioactive levels and radiological hazard assessment associated with exposure to radionuclides from uranium tailings were investigated in this study. Herein, the concentrations of 238 U, 226 Ra, 232 Th, and 40 K in 36 samples including 25 soil and 11 water samples were measured using a low background HPGe semiconductor detector. The radionuclide concentrations were much lower outside the tailings reservoir than inside the reservoir; however, both exceeded the national average and world average values. The mean concentrations of 238 U, 226 Ra, 232 Th, and 40 K in water samples were higher than the WHO guideline levels. The radionuclide transfer factors showed that the radionuclides in soil of the tailings enter the surrounding water. Additionally, the radiological hazard indices around the reservoir were much higher than the worldwide average. Results suggest that the high level of radiation in the tailings reservoir posed a potential threat to the health of the local residents.